High-affinity 1 : 2 recognition based on naphthyl-azocalix[4]arene and its application as a cleavable noncovalent connector in constructing responsive supramolecular polymeric materials - Yao, Shun-Yu; Ying, An-Kang; Geng, Wen-Chao; Chen, Fang-Yuan; Hu, Xin-Yue; Cai, Kang; Guo, Dong-Sheng (Chemical science (Cambridge), 2025)
Macrocyclic hosts which can bind two guests simultaneously with high affinity, such as cucurbit[8]uril, are highly useful for a wide range of applications by acting as noncovalent connectors. However, the integration of stimuli-controlled release properties into such robust noncovalent connectors would be even more desirable. Here, we introduce Naph-SAC4A, a naphthyl-extended deep-cavity azocalix[4]arene with hypoxia-responsiveness, which exhibits exceptional 1 : 2 hosting abilities for organic dyes in aqueous solution with affinities ranging from 10 14 to 10 16 M −2 . Furthermore, Naph-SAC4A was employed as a robust hypoxia-cleavable noncovalent connector to construct linear supramolecular polymers and crosslinked supramolecular hydrogels. Both structures exhibit responsiveness to hypoxic stimuli. With its high-affinity 1 : 2 recognition, unique hypoxia-responsiveness, and easy accessibility, Naph-SAC4A holds great potential for smart supramolecular polymeric materials. Naph-SAC4A forms 1 : 2 host-guest complexes ( K total up to 10 16 M −2 ) with dyes, enabling modular hypoxia-responsive supramolecular polymers and hydrogels. This system shows broad potential in drug delivery, tissue engineering, and imaging diagnostics.